Clients' returning for cervical screening results : a focus group study exploring the reasons why women spontaneously return for their results at the Khayelitsha Cervical Cancer Screening Project - Honikman, Simone (Department of Paediatrics and Child Health, 2015)
Bibliography: leaves 112-123.